Community Empowerment by Utilizing Waste into Plastic Flower Crafts at Sidowaras, Bumi Ratu Nuban Central Lampung - Rizky Hidayatullah; Mai Zuniati; Wiwied Pratiwi; Umar Al Faruq A. Hasyim; Santi Widyawati; Peni Maulita (Yayasan Payungi Smart Madani, 2021)
Located in the lowlands, Sisowaras Village, Bumi Ratu Nuban Subdistrict, has many livelihoods as farmers, where the majority of the population grows rice in the fields. Apart from farmers, there are also many other livelihoods such as traders, livestock breeders, builders, educators and government employees. However, there are still many young people in the Sidowaras village who do not have a livelihood and lack of creativity, so the purpose of this service is to empower the community in utilizing waste into plastic flower crafts. The service method uses the Asset Based Community Development (ABCD) approach by involving members of the Sidowaras village community, Bumi Ratu Nuban District. . The results of this service are community empowerment in terms of utilizing waste into flower crafts and Capacity Building in the Creative Economy Sector for the Sidowaras community through the use of waste into plastic flowers which can increase capacity in terms of creativity of the Sidowaras village community in terms of creative industries that can develop creativity in terms of the economy. Keywords: Community Empowerment, Waste Utilization, Plastic Flowers